A Dyadic Test of the Association Between Trait Self-Control and Romantic Relationship Satisfaction - Zuo, Pei-Ying; Karremans, Johan C.; Scheres, Anouk; Kluwer, Esther S.; Burk, William J.; Kappen, Gesa; Ter Kuile, Hagar (Frontiers in Psychology, 2020)
Previous research has demonstrated that trait self-control is related to a range of positive romantic relationship processes, suggesting that trait self-control should be positively and robustly linked to relationship satisfaction in both partners in a romantic relationship. However, the existing empirical evidence is limited and mixed, especially regarding partner effects (i.e., the effect of one’s self-control on the partner’s relationship satisfaction). With three datasets of heterosexual couples (S1: N = 195 newlyweds, longitudinal; S2: N = 249 couples who transition into first parenthood, longitudinal; S3: N = 929 couples, cross-sectional), the present pre-registered studies examined: 1) the dyadic associations between trait self-control and relationship satisfaction both cross-sectionally and longitudinally, and 2) whether these effects hold when controlling for both partners’ relationship commitment. The results indicated a cross-sectional positive actor effect, some support for a positive cross-sectional partner effect, and only little support for a longitudinal actor (but not partner) effect. After controlling for relationship commitment, all effects of trait self-control on satisfaction diminished, except for a longitudinal actor effect among women in Study 2. Potential explanations for the current results, and implications for theory and practice, are discussed.